An Inquiry into the Validity of Technical Analysis in Financial Markets With the Use of Evolutionary Techniques - Macedo, Luís Manuel Lobato de (2018)
Tese de Doutoramento em Gestão, no ramo de Ciência Aplicada à Decisão, apresentada à Faculdade de Economia da Universidade de Coimbra